Penerapan Sistem Rally Point Terhadap Pola Latihan Pemain Tunggal Pada Klub Bulu Tangkis di Kota Semarang - Muhaimin Ahmad; Metta Christiana; Andi Nurcahyo (Journal of Physical Activity and Sports (JPAS), 2023)
This study aims to determine the application of the rally point system to single player training patterns at badminton clubs in Semarang City. This study uses a qualitative approach. The object of this study is the single player practice patterns at badminton clubs in Semarang City. Sources of information that were the subject of the study were PBSI City Council administrators in Semarang City, coaches and athletes at badminton clubs in Semarang City. The data collection methods used are interviews, observation, and documentation. Data analysis techniques use data triangulation techniques. The results of this study indicate that the rally point system applied to badminton has a direct impact on the pattern of single player play at badminton clubs in Semarang City. The rally point system has an impact on single player training patterns that demand fast, accurate games and good power to win games. The coach has changed the training program from an old model training program that emphasizes endurance and physical strength of players to a training program that emphasizes good speed, accuracy and power. Likewise athletes have adapted to training patterns that emphasize speed, accuracy, and power.